Odpowiedzi

2010-01-01T23:21:24+01:00
2(x-3y)² - 3(x-2y)(x+2y)+12xy=2(x²-2*3xy+9y²)-3(x²-4y²)+12xy=
=2x²-12xy+9y²-3x²+12y²+12xy=-x²+21y²


x=3√2 ,
y=-√2

-x²+21y²=-(3√2)²+21(-√2)²=-9*2+21*2=-18+42=24
2010-01-02T00:17:51+01:00
2(x-3y)² - 3(x-2y)(x+2y)+12xy=
=2(x²-6xy+9y²)-3(x²-4y²)+12xy=
=2x²-12xy+18y²-3x²+12y²+12xy =
= -x²+30y²

Korzystam ze wzorów skróconego mnożenia
(a-b)² = a² - 2ab + b²
(a-b)(a+b) = a² - b²

obliczam dla :
x=3√2 ,
y=-√2

-x²+30y²=
= -(3√2)²+30(-√2)²=
= -9*2+30*2=
= -18+60=
= 42